2019
DOI: 10.3389/fphar.2019.01472
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Lopinavir/Ritonavir- and Efavirenz-Based Initial Antiretroviral Therapy in HIV-1-Infected Patients in a Tertiary Care Hospital in Beijing, China

Abstract: Background: Lopinavir/ritonavir (LPV/r) is a major antiretroviral treatment in China, but little is known about the performance of first-line LPV/r-based regimen in treatment-naïve patients with human immunodeficiency virus type 1 (HIV-1) infection. This study aims to assess the efficacy and adverse effect events of LPV/r plus lamivudine and tenofovir or zidovudine as an initial antiretroviral treatment in HIV-1-infected individuals for whom cannot take efavirenz (EFV) or is allergic to EFV. Methods:We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 35 publications
0
33
0
2
Order By: Relevance
“…By February 4, 2020, two patients were confirmed 2019-nCoV negative and one patient was virus-negative at the first test. Lopinavir/ ritonavir (Kaletra ® ) is a human immunodeficiency virus (HIV) medicine used in combination with other medicines to treat adults and children over 14 days of age who are infected with HIV-1 (7). It was revealed that lopinavir/ritonavir among SARS-CoV patients was associated with substantial clinical benefit (fewer adverse clinical outcomes) (8).…”
Section: Treatment and Clinical Outcomesmentioning
confidence: 99%
“…By February 4, 2020, two patients were confirmed 2019-nCoV negative and one patient was virus-negative at the first test. Lopinavir/ ritonavir (Kaletra ® ) is a human immunodeficiency virus (HIV) medicine used in combination with other medicines to treat adults and children over 14 days of age who are infected with HIV-1 (7). It was revealed that lopinavir/ritonavir among SARS-CoV patients was associated with substantial clinical benefit (fewer adverse clinical outcomes) (8).…”
Section: Treatment and Clinical Outcomesmentioning
confidence: 99%
“…11 Lopinavir and Ritonavir are anti-human immunodeficiency virus (HIV) protease inhibitor, which are also used to treat HIV-1 in adults and children above 14 days of age. 22 That fewer adverse clinical outcomes were reported among SARS-CoV patients revealed that lopinavir/ritonavir benefited the patients in clinical practice substantially. 23 None of the 32 patients required intensive care or mechanical ventilation or had any severe complications.…”
Section: Discussionmentioning
confidence: 99%
“…Interferon-α is a broad-spectrum antiviral drug previously used for viral hepatitis, and could also potentially block viral replication of SARS-COV [22]. Lopinavir/ritonavir are antiviral agents used in treating Human Immunodeficiency Virus (HIV) infections [23], and are HIV protease enzyme inhibitors that result in the formation of non-infectious viral particles. Lopinavir/ritonavir have shown anti-SARS-CoV activity in clinical trials and in vitro studies [24].…”
Section: Consequences Of the Hypothesis And Discussionmentioning
confidence: 99%